Einstök’s customer-based brand equity in the Icelandic & Swedish market : a perception-based application of Keller’s CBBE pyramid - Jannika Yasmine Lövendahl 1990- (2017)
This is a perception-based application of Kevin Lane Keller’s Customer-based brand equity (CBBE) Pyramid in two Nordic markets; Iceland and Sweden. The CBBE of the Icelandic craft beer brand Einstök was investigated through the chosen framework. Interviews with company representatives and focus groups with consumers from the target group the “Modern Viking” gave answers to the research questions; What are the differences in brand equity between Iceland and Sweden?; Is the “Modern Viking” perceiving the brand identity of the brand in the same way as Einstök is trying to communicate it?; What are the most mentioned brand features/associations of the brand Einstök in Iceland compared to Sweden? And What are the consumers’ experienced brand perception of Einstök in Iceland compared to Sweden? The findings from focus groups were first analysed through thematic analysis. The adjectives used to explain the Einstök brand was categorised into matching themes in form of mind maps. After the mind maps were created, a word cloud for each focus group was created. When the analysis was completed, the following answers could be withdrawn in order to answer the research questions; Due to different level of exposure of the brand in the home market Iceland compared to the Swedish market; consumers show a different level of brand equity. Findings from the interviews with the company representatives show similarities in ways to express the brand identity of Einstök. The most common themes used by Icelandic consumers in order to explain the brand are attractive, authentic, Icelandic, reliable and tasty. Attractive, character, creative, Icelandic and quality are the most common words used by Swedish consumers when explaining the Einstök brand. Keywords: Customer-based Brand Equity, Focus Groups, Qualitative Study, Thematic Analysis, Craft Beer